Influência do teor de cobre no tratamento térmico de solubilização e envelhecimento artificial de ligas Al-Cu fundidas - Ribeiro, Bruno de Rosso (2015)
The main objective of this work was to analyze the solutioning and artificial aging heat treatments of aluminum-copper casting alloys, composed of two distinctive copper contents: 2.5% and 3.5%, unidirectionally solidified in an instrumented metal-mold system. Solidification parameters such as solidification velocities, thermal gradients and cooling rates were determined from cooling curves obtained by thermal analysis. Macrostructures and microstructures of ingots were analyzed in relation to parameters such as columnar-equiaxed transition (CET) and the secondary dendrite arm spacing (SDAS). The heat treatments were performed in order to better understand the solutioning and artificial aging processes of copper in the aluminum matrix. The results concerning to the solidification parameters have permitted to obtain expressions for solidification velocities, thermal gradient and cooling rates as a function of examined alloys. Relationship among solidification conditions, structural formation and hardness were also obtained [SDAS=f(TRL); HB=f(SDAS)]. The Al-3.5wt%Cu alloy has show smaller dendritic arm spacing (10%), higher columnar zone (12%), higher hardness in the as-cast condition (8%), as well as better response to the heat treatments than the examined Al-2.5wt%Cu.